Pengenalan Dan Pelatihan Implementasi Tool Mendeley Guna Efektivitas Penyususnan Karya Ilmiah - Desti Mualfah; Harun Mukhtar; Soni Soni; Sunanto; Yoze Rizki; Reny Medikawati Taufik; Febby Apri Wenando; Diah Angraina Fitri (Jurnal Pengabdian UntukMu NegeRI, 2022)
The management of citations and reference articles from various scientific journals must be mastered by students in order to produce good scientific works. One of the tools that can be used in managing scientific work citations is the Mendeley tool. The Mendeley tool provides a lot of convenience in improving the quality of writing scientific articles, namely making it easier for students to make citations and bibliography. This training is held at the Universitas Islam Indragiri (UNISI) by involving students who will carry out final research (scripts).